DESAIN PENELITIAN SURVEY - Arif Wahyudi; Dina Hermina; Salamah (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study discusses the importance of sound survey research design in producing valid, reliable and relevant data. Through an analysis of the fundamental principles of survey design, this study emphasises that careful planning and systematic implementation at every stage of the research are key factors in minimising errors and bias. Furthermore, survey research plays a strategic role as a method capable of providing accurate information to support the decision-making process. By applying an appropriate survey design, researchers not only improve the quality of research outcomes but also make a significant contribution to the advancement of scientific knowledge and professional practice across various fields.